THE IMPACT OF THE USE OF INFORMATION TECHNOLOGY ON THE ACCOUNTING PROFESSION IN THE ACCOUNTING LABOR MARKET IN THE KURDISTAN REGION, A FIELD STUDY OF PROFESSIONALS IN COMPANIES AND ACADEMICS IN ACCOUNTING DEPARTMENTS IN ERBIL GOVERNORATE - Ahmed , Ramyar; Ibrahim, Basm (Humanities Journal of University of Zakho, 2024)
This study aims to explore the impact of the use of information technology on the accounting profession in the labor market in the Kurdistan Region, with a special focus on the opinions of professionals working in companies and academics in accounting departments in Erbil Governorate. The main problem addressed by the study is based on the challenge that accounting education faces in keeping pace with rapid developments in information technology and integrating them effectively within educational programs. In light of the significant expansion of the use of technology in various areas of life, including accounting, the urgent need for university accounting departments to provide the necessary scientific and practical skills to students is highlighted, to qualify them to work in an advanced technological accounting environment. Accordingly, the basic hypothesis of the study was formulated: “Using technology Information in accounting education raises the academic and professional competence of students in accounting departments, enabling them to keep pace with the requirements of the contemporary labor market in the Kurdistan region. To achieve the objectives of the study and examine the hypothesis, the descriptive analytical approach was adopted, which is suitable for studying the relationship between the use of information technology in accounting education and the competence of graduates. The descriptive aspect includes the use of relevant scientific literature and references, while in the analytical aspect, data is collected through questionnaires directed to a sample of the study, and analyzed using the Statistical Package for the Social Sciences (SPSS) program. The results highlight the importance of information technology in accounting and confirm the existence of a relationship There is a strong connection between the technological qualification of accountants and the actual reality of their profession in the region. Therefore, the study recommends the need to pay attention to continuously evaluating accounting educational programs and developing them to meet the changing needs of the labor market, including providing specialized training courses in information technology, modernizing the technological infrastructure, and enhancing cyber security for data. Accounting. These measures will contribute to improving the competence and skills of accounting graduates tobetter prepare them to face contemporary challenges in the accounting profession.